Dynamic modeling of a hybrid electric system based on an anion exchange membrane fuel cell. Issue 1 (1st January 2017) - Fragiacomo, Petronilla; Astorino, Emilio; Chippari, Giorgio; De Lorenzo, Giuseppe; Czarnetzki, Walter Theodor; Schneider, Waldemar
Abstract: The main topic of this paper is the dynamic modeling of a hybrid energy system based on an anion exchange membrane fuel cell (AEMFC). The objective was to develop a dynamic model, able to describe the system behavior and the response of components to sudden load changes. The overall model design includes other different subsystems, represented by electric dipoles or double dipoles. In addition to the two power sources, AEMFC and battery pack, there is a DC-DC buck converter, interjected between them, whose function is to decrease AEMFC voltage to bus voltage set by a battery pack and to smooth this voltage, thereby serving the load properly. Above all, there is a step time-varying dc load and a power management block, for the managing of energy flows through the system. The whole model was implemented in Matlab–Simulink environment. The main outputs of DC-DC buck converter and battery dynamic models were validated respectively with the data of other equally detailed reference simulation models and with experimental data found in the literature. In this paper, the design of a discrete intervals power management strategy to manage the connection/disconnection of the AEMFC was made and the hybrid managed energy system calculation code was used to evaluate the time trends of AEMFC and battery pack electric powers, of battery pack state of charge, of DC-DC buck converter and entire hybrid system efficiencies for different initial battery pack states of charge and different step time-varying dc loads.